2021
DOI: 10.3346/jkms.2021.36.e170
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Health Care Workers during the COVID-19 Pandemic in Korea: a Qualitative Study

Abstract: Background During the coronavirus disease 2019 (COVID-19) pandemic, health care workers (HCWs) have faced multiple physical and psychological challenges while carrying out their duties. In this study, we examined the experiences of specific groups of HCWs during the pandemic. Methods From 18 November to 30 December 2020, we conducted a qualitative study using semi-structured, face-to-face interviews with four groups of 14 HCWs in three cities (Seoul, Daegu, and Gwangju)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 46 publications
3
33
0
1
Order By: Relevance
“…Further, healthcare workers suffer from excessive workloads leading to health-related issues, psychological stress and burnout, lifestyle changes, and fear of infection when treating COVID-19 patients. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Further, healthcare workers suffer from excessive workloads leading to health-related issues, psychological stress and burnout, lifestyle changes, and fear of infection when treating COVID-19 patients. 2 …”
Section: Introductionmentioning
confidence: 99%
“…These are not far from previous qualitative studies about HCWs under other COVID-19 pandemic situations. ( Aughterson et al., 2021 ; Banerjee et al., 2021 ; J.Y. Lee et al., 2021 ; Rathnayake et al., 2021 ) However, the HCWs in this study had worked in a critical situation, because they had cared for in-patients with severe mental illnesses without a break.…”
Section: Discussionmentioning
confidence: 99%
“…It was also interesting that the higher scores of a questionnaire item regarding work experience involving ‘If optional, I would have chosen to work in another unit’ had a significant effect in increasing the emotional distress, and it may be related to occupational satisfaction. Lee et al 10 reported that occupational stress consists of four domains overwhelmed by heavy workloads, fear of infection, lifestyle changes, and psychological and physical struggles in a qualitative analysis after interviewing HCWs who directly or indirectly cared for patients during the COVID-19 epidemic. Regarding this, additional research is needed to identify the HCWs condition by as subdividing work stress domain and quantifying the work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, HCWs are at a high risk of infection, and the fear of infection can pose a psychological burden. 10 Evidence suggests that frontline HCWs inevitably face tremendous psychological burden in an infectious disease environment, similar to severe acute respiratory syndrome (SARS). 11 12 During recent Ebola outbreak, an unprecedented number of HCWs were infected, and survivors endured higher rates of post-traumatic stress disorder (PTSD).…”
Section: Introductionmentioning
confidence: 99%